2008
DOI: 10.1016/j.bcp.2008.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Role of mitochondrial dysfunction in cellular responses to S-(1,2-dichlorovinyl)-l-cysteine in primary cultures of human proximal tubular cells

Abstract: The nephrotoxic metabolite of the environmental contaminant trichloroethylene, S-(1,2-dichlorovinyl)-L-cysteine (DCVC), is known to elicit cytotoxicity in rat and human proximal tubular (rPT and hPT, respectively) cells that involves inhibition of mitochondrial function. DCVC produces a range of cytotoxic and compensatory responses in hPT cells, depending on dose and exposure time, including necrosis, apoptosis, repair, and enhanced cell proliferation. The present study tested the hypothesis that induction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 41 publications
5
29
1
Order By: Relevance
“…Our results of immunohistochemistry showed that hesperidin alleviates the effect of TCE-induced nephrotoxicity. Expression of caspase-3 was assessed and was found to be elevated in the TCEtreated group compared to the control group, signifying that TCE activates caspase-3, thus, in agreement with earlier reports [65]. Treatment with hesperidin showed reduced caspase-3 expression in the low dose group, which was further downregulated and was found to be almost similar to the control group with high-dose hesperidin pretreatment.…”
Section: Discussionsupporting
confidence: 85%
“…Our results of immunohistochemistry showed that hesperidin alleviates the effect of TCE-induced nephrotoxicity. Expression of caspase-3 was assessed and was found to be elevated in the TCEtreated group compared to the control group, signifying that TCE activates caspase-3, thus, in agreement with earlier reports [65]. Treatment with hesperidin showed reduced caspase-3 expression in the low dose group, which was further downregulated and was found to be almost similar to the control group with high-dose hesperidin pretreatment.…”
Section: Discussionsupporting
confidence: 85%
“…The effective DCVC concentrations for inhibition of LTA, LPS, and GBS stimulation of TNF-α release in the present study were at or near the lowest bioactive concentrations of DCVC reported in kidney cells [57]. The relevance of concentrations of DCVC to human exposure is difficult to establish due to insufficient data [15].…”
Section: Discussionmentioning
confidence: 90%
“…DCVC is considered to cause renal cell injury after metabolic activation by cysteine conjugate β-lyase (Cummings and Lash, 2000;Tateishi et al, 1978;Tomisawa et al, 1986). Current understanding of the mechanism of DCVC-induced renal injury derives primarily from studies on isolated proximal tubular cells (Cummings and Lash, 2000;Lash et al, 2014;Xu et al, 2008) or subcellular fractions of renal cortical homogenates from rats, rabbits, and other non-human mammals (Davis and Petry, 1994;Lash et al, 2001;Wolfgang et al, 1990). We also reported subchronic nephrotoxic effects of DCVC in mice (Shirai et al, 2012).…”
Section: Introductionmentioning
confidence: 63%